Economic impact of coconut diseases and their management through sustainable and eco-friendly approaches: An extension report on technology dissemination to boost productivity and resilience in coconut plantations of Andhra Pradesh - Rao, V Govardhan; Neeraja, B; Rani, A Snehalatha; ChalapathiRao, N B V; V, Anoosha; A, Kireeti; S, Sumitha; Jerard B, Augustine (Indian Journal of Plant Protection, 2025)
Coconut farming is crucial to Andhra Pradesh’s economy, with the state significantly contributing to India’s production. Over the past two decades, major diseases like basal stem rot, bud rot, and stem bleeding have affected coconut crops. Basal stem rot, the most prevalent, caused yield losses up to 51% in neglected conditions, with an average incidence of 14.11%. Bud rot led to up to 31% yield loss in young gardens, while stem bleeding caused 18% yield loss. However, the adoption of timely technologies and bio agents has helped reduce these losses. Basal stem rot incidence decreased from 20.60% to 8.28%, bud rot from 25.63% to 0.86%, and stem bleeding from 10.21% to 4.35%. These measures saved farmers significant losses, including Rs. 4412.71 per acre from basal stem Rot, Rs. 10,018 per acre from stem bleeding, and Rs. 2741 per acre from bud rot. By 2020, preventive actions saved nearly ₹30 crore across 41,513 acres from basal stem rot, 9,379 acres from stem bleeding, and 2,530 acres from bud rot, benefiting farmers in districts of East Godavari and Srikakulam.